Peran Sertifikasi Halal dalam Meningkatkan Kepercayaan Konsumen dan Daya Saing UMKM Pangan Desa Cijurey - Sofi Yulloh, Muhammad; Muawiyah; Nuraini, Ayi; Lisnawati; Apriandinata, Irsan; Agustin, Eki (Universitas KH. Mukhtar Syafaat (UIMSYA), 2025)
The increasing awareness of halal consumption among Muslim communities has made halal certification a crucial factor influencing consumer trust and competitiveness in the food industry, particularly for micro, small, and medium enterprises (MSMEs). This study aims to examine the role of halal certification in enhancing consumer confidence and improving the competitive advantage of food-based MSMEs in Cijurey Village. The research employed a qualitative descriptive method through interviews, fi eld observations, and document analysis with selected MSME owners and consumers. Findings reveal that halal certification not only strengthens consumer trust by ensuring product safety, cleanliness, and religious compliance, but also improves the market positioning of certified MSMEs, making them more competitive both locally and regionally. The certification process further motivates business owners to maintain higher production standards, expand market access, and meet broader consumer expectations. This study concludes that halal certification plays a strategic role in sustaining business growth and community welfare, while also serving as an effective instrument for increasing consumer loyalty. The implication of this research highlights the need for continuous support and facilitation of halal certification programs to empower rural-based MSMEs and improve the resilience of the local economy.